A novel bipolar D–π–A type phenanthroimidazole/carbazole hybrid material for high efficiency nondoped deep-blue organic light-emitting diodes with NTSC CIEy and low efficiency roll-off. Issue 45 (13th November 2017) - Tan, Yu; Zhao, Zifeng; Shang, Liang; Liu, Yang; Wei, Chen; Li, Jiayi; Wei, Huibo; Liu, Zhiwei; Bian, Zuqiang; Huang, Chunhui
Abstract : Nondoped OLEDs utilizing a new emitter exhibited EL with NTSC CIE y and high EQEmax (5.80%) with low efficiency roll-off. Abstract : Tremendous efforts have been devoted to developing efficient deep-blue organic light-emitting diodes (OLEDs), but deep-blue OLEDs with high external quantum efficiency (EQE) and CIE y < 0.10 (Commission Internationale de L'éclairage (CIE)), especially matching the National Television System Committee (NTSC) standard blue CIE ( x, y ) coordinates of (0.14, 0.08), are still limited. Herein, we report the synthesis, photophysical properties, thermostability and electrochemical characterization of two phenanthroimidazole/carbazole-based compounds (CBPMCN and CPBPMCN). Single X-ray crystal data of CPBPMCN indicate that it adopts a severely twisted structure, resulting in a low degree of intermolecular π–π stacking, which is appropriate to be employed as a nondoped deep-blue emitter. Nondoped devices based on CPBPMCN exhibited deep-blue electroluminescence (EL) with CIE coordinates of (0.15, 0.08), which is extremely close to the NTSC standard blue. Meanwhile, the devices showed impressively high EQEmax up to 5.80% with relatively small efficiency roll-off.